GAGASAN TEOLOGI ISLAM TERHADAP PLURALITAS MASYARAKAT BANGSA - Imam Ghazali Said (Studia Philosophica et Theologica, 2003)
Plurality is a challenge. Though Islam is normatively a tolerant religion, the concept of plurality needs to be discussed in the Islamic world. The article draws theologically plurality in the Islamic perspectives. It shows that in the Quran what we call plurality is theologically inserted. The Indonesian Moslems promote plurality in their lives and tolerant witness to other people of the different religions.